Education, Health Screening, and Distribution of Functional Emergency Food for Health Recovery for the Elderly After the Cianjur Earthquake - Annis Catur Adi; Salisa, Wizara; Rasyidi, Mohammad Fahmi; Isaura, Emyr Reisha; Rachmawati, Heni (Universitas STRADA Indonesia, 2024)
Adi, A. C., Rachmawati, H., Hidayati, D., & Isaura, E. R. (2022). Characteristics Of High Protein Product-Derived Catfish Mixed With Fermented Sweet Potato Flours And Its Impact On Malnourished Rats. Sains Malaysiana. Ariyanti, R., Preharsini, I. A., & Sipolio, B. W. (2020). Health Education in Efforts to Prevent and Control Hypertension in the Elderly. To Maega : Jurnal Pengabdian Masyarakat, 3(2), 74. https://doi.org/10.35914/tomaega.v3i2.369. Faisal, F, & Manalu, M. (2023). Education on Elderly Preparedness in Facing Flood Disasters in the Working Area of ​​Hutabalang Health Center, Badiri District. Jurnal Kreativitas Pengabdian Kepada Masyarakat, 6(11). https://doi.org/10.33024/jkpm.v6i11.12497. Gallagher, D., Heymsfield, S. B., Heo, M., Jebb, S. A., Murgatroyd, P. R., & Sakamoto, Y. (2000). Healthy percentage body fat ranges: an approach for developing guidelines based on body mass index. The American Journal of Clinical Nutrition, 72(3), 694–701. https://doi.org/10.1093/ajcn/72.3.694. Indonesian Health Ministry. (2016). The Elderly Book. Jakarta: Indonesian Health Ministry. Indonesian Health Ministry: Prevention and Control of Non-Communicable Diseases. (2018). Hypertension Classification. Indonesian Health Ministry. (2020). Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2020 concerning Children's Anthropometric Standards. Kıskaç, M., Soysal, P., Smith, L., Capar, E., & Zorlu, M. (2022). What is the Optimal Body Mass Index Range for Older Adults? Annals of Geriatric Medicine and Research, 26(1), 49–57. https://doi.org/10.4235/agmr.22.0012. Lukvianti, F., Mailani, F., & Ananda, Y. (2023). The Effect Of Giving Earthquake Disaster Preparedness Education To The Elderly In Parupuak Tabing Village, Padang City. JINTAN: Jurnal Ilmu Keperawatan. Malini, H., Fitri, Y., & Krisdianto, B. F. (2023). Disaster Preparedness Education to Improve Elderly Perception In Pasia Nan Ti Go Village, Koto Tangah District, Padang. Buletin Ilmiah Nagari Membangun, 6(3):187-197. McCarthy, H. D., Cole, T. J., Fry, T., Jebb, S. A., & Prentice, A. M. (2006). Body fat reference curves for children. International Journal of Obesity, 30(4), 598–602. https://doi.org/10.1038/sj.ijo.0803232. [MCGA] Meteorology, Climatology and Geophysics Agency. (2022). Cianjur Earthquake Analysis (West Java) Mw 5.6. [NBDM] National Board for Disaster Management. (2023). Number of Disasters in Indonesia 2019-2023. [NBDM] National Board for Disaster Management. (2023). Categories of Disaster Victims in Indonesia in 2023. Nuraini, B. (2015). RISK FACTORS OF HYPERTENSION. Jurnal MAJORITY , 4(5), 10–19. Nurhasanah, A., & Nurdahlia, N. (2020). Health Education Increases Family Knowledge and Skills in Preventing Falls in the Elderly. JKEP, 5(1), 84–100. https://doi.org/10.32668/jkep.v5i1.359. Porter Starr, K. N., & Bales, C. W. (2015). Excessive Body Weight in Older Adults. Clinics in Geriatric Medicine, 31(3), 311–326. https://doi.org/10.1016/j.cger.2015.04.001 Shapo, L., Pomerleau, J., & McKee, M. (2003). Epidemiology of hypertension and associated cardiovascular risk factors in a country in transition: a population based survey in Tirana City, Albania. Journal of Epidemiology & Community Health, 57(9), 734–739. https://doi.org/10.1136/jech.57.9.734. Siregar, P. A., Simanjuntak, S. F. S., Br. Ginting, F. H., Tarigan, S., Hanum, S., & Utami, F. S. (2020). Analysis of Risk Factors For Hypertension Incidents In Coastal Communities of Medan City (Socio-Cultural Aspects of Coastal Communities). Jurnal Pembangunan Perkotaan, 8(1), 1–7. Siregar, P. A., Simanjuntak, S. F. S., Ginting, F. H., Tarigan, S., Hanum, S., & Utami, F. S. (2020). Physical Activity, Consumption of Salty Foods and the Occurrence of Hypertension in Coastal Communities in Medan City. Jurnal Ilmiah Kesehatan (JIKA), 2(1), 1–8. https://doi.org/10.36590/jika.v2i1.34. Wahyuni, Yusran, S., & Harleli. (2020). The Relationship Between Diet Patterns and Lifestyle with The Incidence of Hypertension In Farmers In The Work Area of Basala Community Health Center, South Konawe Regency In 2020. Jurnal Gizi dan Kesehatan Indonesia, 1(2), 65–73.